(untitled) (Gestión y Gerencia, 2019)
The world is undergoing times of radical change. The last few decades have witnessed economical, political and social changes as a result of the installation and deployment of new information and communications technologies. Venezuelan researcher Carlota Perez, in her globally recognized book “Technological Revolutions and Financial Capital: Dynamics of Bubbles and Golden Ages”, (Edward Elgar, 2002), shows how humanity has developed in cycles of about half a century based on the emergence of new technological vectors. According to Perez, the world has witnessed five such technological revolutions since the “Industrial Revolution”, which have been responsible for the growth and transformation of the world economy along the last 240 years. Carlota Perez also argues that, in each of them, new technologies boosted a deep change in organizational strategies, management practices and occupational and social behaviors to successfully take advantage of the opportunities that each one of them offered. These changes were of such a profound significance that, in each occasion, they drove a total transformation of the nature and content of individual attitudes and behaviors, not only in the workplace but also in all areas of human activity; social, communitarian even personal. A change of such wide implications, that Perez has called the new techno-economic paradigm “a change of common sense”. This previous foreword is important to put in perspective the present moment along the evolution of the current Revolution of Information and Telecommunications; a transformation process that the world has been undergoing since the beginning of the popularization of the personal computer and more intensely since the birth of the Internet. A process that, as any viral diffusion, begins in the thoughts and actions of pioneering minds who, be it by visioning capacity or acute intuitive sensibility, are capable of recognizing, adopting, demonstrating and diffusing the development opportunities associated with the new technological vector and with the changes in thinking and behaving that they demand.